Effect of Technology Enhanced Language Learning on EFL Reading Comprehension at Tertiary Level - Imtiaz, Hassan Taj; Fatimah, Ali; Muhammad Aslam, Sipra; Waqar, Ahmad (SSRN, 2017)
The study investigated the impact of the affordance of computer assisted language learning (CALL) and mobile assisted language learning (MALL) on EFL reading comprehension at tertiary level. Pre-formed intact groups were used to conduct this quasi-experimental study. It used a pretest and post-test control group design. The participants were 122 first year university students. Computer-based reading comprehension exercises were used as intervention that lasted for six weeks. Vocabulary was pre-taught through WhatsApp. Post-test results of the reading comprehension achievement test revealed that the treatment group outperformed their counterparts in the control group. The results indicate the significance of technology incorporation in language learning process. The study shows the effective use of technology in EFL reading instruction. It works best when integrated in the instructional scheme. Results of the study also suggest that freely available technological resources can be used to create a conducive reading environment. The study needs to be replicated with bigger sample and longer period of intervention for more accurate results.